A yellowing-resistant quartz glue resin and preparation method thereof
By adding modified hollow microbeads and antioxidants to the quartz glue resin and combining quartz filler, the problem of existing quartz glue resin being prone to yellowing under ultraviolet rays and heat is solved, and its yellowing resistance is significantly improved variable and mechanical properties.
Patent Information
- Application Number
- CN202411334739.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Existing quartz glue resins are prone to yellowing under ultraviolet rays and heat, which affects the aesthetics and durability of quartz stone.
Modified hollow microbeads and antioxidants are uniformly dispersed in the epoxy resin, and a stable three-dimensional network structure is formed by curing agent. Quartzite is used as a filler to improve the mechanical properties of the resin.
It significantly improves the yellowing resistance and mechanical properties of quartz glue resin and extends its service life.
Smart Images

Figure BDA0005057958310000061 
Figure BDA0005057958310000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of resins, in particular to a yellowing-resistant quartz glue resin and a preparation method thereof. Background Art
[0002] Existing quartz stone slabs have the advantages of rich colors, outstanding product performance, high hardness, scratch resistance, pollution resistance, low water absorption and low shrinkage. They are widely used in industrial production and daily life as decorative materials for floor tiles, walls, window sills, kitchen countertops, etc.
[0003] Quartz glue is an adhesive commonly used in the construction industry, mainly used to bond quartz slabs. Quartz glue has the characteristics of high strength, wear resistance, acid and alkali resistance. Most of the quartz glue resins currently on the market use epoxy resin as the base material, but the unsaturated bonds of epoxy resin are easily oxidized under the action of ultraviolet rays, heat and other factors, causing yellowing, which affects the beauty and durability of the quartz stone. Summary of the invention
[0004] In order to improve the yellowing resistance of quartz glue resin, the present application provides a yellowing-resistant quartz glue resin and a preparation method thereof.
[0005] In the first aspect, the present application provides a yellowing-resistant quartz glue resin using the following technical method:
[0006] A yellowing-resistant quartz glue resin comprises the following raw materials in parts by weight: 40-60 parts of epoxy resin; 2-6 parts of curing agent; 20-40 parts of quartz; 20-40 parts of modified hollow microspheres; and 1-3 parts of antioxidant. The modified hollow microspheres are made of the following raw materials: hollow microspheres, dilute sulfuric acid solution, lanthanum chloride solution and aluminum chloride.
[0007] By adopting the above technical scheme, epoxy resin is used as the main raw material, and the epoxy resin itself is prone to yellowing under ultraviolet irradiation. The present application adds modified hollow microspheres and antioxidants to be evenly dispersed in the epoxy resin to improve the fluidity of the epoxy resin. The epoxy resin and the modified hollow microspheres are formed into a stable three-dimensional network structure through the curing agent. Quartz stone is used as a filler to improve the mechanical properties of the resin. The mutual coordination of various components helps to improve the yellowing resistance of the epoxy resin.
[0008] Preferably, the preparation method of the modified hollow microspheres is: 15-45 parts by weight of hollow microspheres and 60-80 parts by weight of dilute sulfuric acid solution are mixed and stirred, washed after centrifugation, mixed and stirred with 40-60 parts by weight of lanthanum chloride solution after drying, and then 10-30 parts by weight of aluminum chloride are added and continued to stir, washed after centrifugation, and dried, and ground to obtain modified hollow microspheres.
[0009] By adopting the above technical scheme, the hollow microspheres are pretreated with sulfuric acid, the impurities on the surface of the hollow microspheres are cleaned with a dilute sulfuric acid solution to enhance the surface activity, the lanthanum aluminum intercalation modification is performed to form oxides on the surface of the hollow microspheres, the dispersibility of the hollow microspheres is improved, and the compatibility of the hollow microspheres with the epoxy resin is enhanced, which helps to improve the yellowing resistance and wear resistance of the quartz stone glue resin.
[0010] Preferably, the particle size of the hollow microspheres is in the range of 20-40 μm.
[0011] By adopting the above technical solution, controlling the particle size range of the hollow microspheres can make the hollow microspheres more evenly dispersed on the epoxy resin, further enhancing the bonding force between the hollow microspheres and the epoxy resin, and helping to improve the thermal stability and yellowing resistance of the material.
[0012] Preferably, the weight ratio of the hollow microspheres, lanthanum chloride solution and aluminum chloride is 1:(1.8-1.9):(0.4-0.5).
[0013] By adopting the above technical scheme, when the hollow microspheres, lanthanum chloride solution and aluminum chloride are in a specific weight ratio, the hollow microspheres themselves have high mechanical properties. After being modified by the lanthanum chloride solution, the hollow microspheres can significantly improve the interfacial compatibility with the epoxy resin substrate, enhance the bonding force between the filler and the substrate, and help improve the thermal stability and yellowing resistance of the material.
[0014] Preferably, the epoxy resin is a modified epoxy resin, and the preparation method of the modified epoxy resin is: 10-30 parts by weight of Chenopodium album and 40-80 parts by weight of anhydrous ethanol are mixed and heated, 2-6 parts by weight of a titanate coupling agent are added, stirred, filtered and dried, and then 20-40 parts by weight of an epoxy resin are added, stirred, and allowed to stand to obtain the modified epoxy resin.
[0015] By adopting the above technical scheme, the present application reacts the titanate coupling agent with the surface hydroxyl group of the silique, cross-links the interface of the silique and the epoxy resin, enhances the interfacial bonding ability of the silique and the epoxy resin, enhances the interaction force between molecules, thereby improving the thermal stability of the epoxy resin, and further improving the yellowing resistance of the quartz glue resin.
[0016] Preferably, the weight ratio of the silique, titanate coupling agent and epoxy resin is 1:(0.135-0.18):(1.6-1.8).
[0017] By adopting the above technical scheme, when the silique, titanate coupling agent and epoxy resin are in a specific weight ratio, the titanate coupling agent forms chemical bonds with the silique and the epoxy resin through different functional groups at both ends, thereby improving the interfacial compatibility between the silique and the epoxy resin matrix, improving the rheological properties of the epoxy resin, and making the modified epoxy resin have better yellowing resistance. The silique contains flavonoids and alkaloid compounds, which have certain antibacterial activity, thereby improving the antibacterial properties of the quartz glue resin.
[0018] Preferably, the weight ratio of the modified epoxy resin, quartz stone and modified hollow microspheres is 1:(0.42-0.48):(0.64-0.72).
[0019] By adopting the above technical scheme, when the modified epoxy resin, quartz stone and modified hollow microspheres are in a specific weight ratio, the quartz stone and modified hollow microspheres are used as fillers to enhance the bonding force between the quartz stone and modified hollow microspheres and the epoxy resin, and improve the yellowing resistance and mechanical properties of the glue resin.
[0020] Preferably, the curing agent is one of maleic anhydride and phthalic anhydride.
[0021] Preferably, the antioxidant is one of the antioxidant BHT and the antioxidant BHA.
[0022] By adopting the above technical solution and selecting suitable curing agent and antioxidant, it is helpful to prepare quartz glue resin with better yellowing resistance.
[0023] In the second aspect, the present application provides a method for preparing a yellowing-resistant quartz glue resin using the following technical solution:
[0024] A method for preparing yellowing-resistant quartz glue resin comprises the following steps: mixing epoxy resin, quartz and modified hollow microspheres, heating and stirring, adding a curing agent and an antioxidant after cooling, and continuing to stir, and obtaining the yellowing-resistant quartz glue resin after cooling.
[0025] By adopting the above technical scheme, the quartz resin can be prepared by simply mixing the raw materials of each component. The method has simple steps, and the prepared quartz resin has good yellowing resistance.
[0026] In summary, this application has the following beneficial technical effects:
[0027] 1. Epoxy resin is the main raw material, and epoxy resin itself is prone to yellowing under ultraviolet irradiation. The present application adds modified hollow microspheres and antioxidants to be evenly dispersed in the epoxy resin to improve the fluidity of the epoxy resin. The epoxy resin and the modified hollow microspheres are formed into a stable three-dimensional network structure through the curing agent. Quartz stone as a filler can improve the mechanical properties of the resin. The mutual coordination of various components helps to improve the yellowing resistance of the epoxy resin.
[0028] 2. The hollow microspheres are pretreated with sulfuric acid, and the impurities on the surface of the hollow microspheres are cleaned with dilute sulfuric acid solution to enhance the surface activity. The lanthanum aluminum intercalation modification forms oxides on the surface of the hollow microspheres, improves the dispersibility of the hollow microspheres, and enhances the compatibility of the hollow microspheres with epoxy resin, which helps to improve the yellowing resistance and wear resistance of the quartz glue resin. DETAILED DESCRIPTION
[0029] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0030] Example
[0031] Example 1
[0032] A method for preparing a yellowing-resistant quartz glue resin comprises the following steps: 40g of epoxy resin, 20g of quartz stone, and 20g of modified hollow microspheres are put into a stirrer, mixed and stirred for 10 minutes at a speed of 1500r / min and a temperature of 65°C, and then cooled to room temperature, 2g of curing agent and 1g of antioxidant are added, and the temperature is raised to 40°C and stirred for 10 minutes, and then cooled to room temperature to obtain a yellowing-resistant quartz glue resin. The curing agent is maleic anhydride, the antioxidant is antioxidant BHT, and the epoxy resin is purchased from Guangzhou Sanchang Chemical Co., Ltd., with a brand of E-51.
[0033] The preparation method of the modified hollow microspheres is as follows: 15 g of hollow microspheres and 60 g of 15% dilute sulfuric acid solution are mixed and stirred on a magnetic stirrer for 30 minutes, centrifuged by a centrifuge to remove the supernatant, washed with distilled water, transferred to an electric constant temperature blast drying oven, dried at a temperature of 80°C for 4 hours, mixed and stirred with 40 g of 0.2 mol / L lanthanum chloride solution at room temperature for 30 minutes, then 10 g of aluminum chloride is added and stirred for 30 minutes, washed with distilled water after centrifugation, and dried in an oven at a temperature of 80°C for 3 hours, and ground to obtain modified hollow microspheres.
[0034] Example 2
[0035] A method for preparing a yellowing-resistant quartz glue resin comprises the following steps: 60g of epoxy resin, 40g of quartz stone, and 40g of modified hollow microspheres are put into a stirrer, mixed and stirred for 10 minutes at a speed of 1500r / min and a temperature of 65°C, and then cooled to room temperature, 6g of curing agent and 3g of antioxidant are added, and the temperature is raised to 40°C and stirred for 10 minutes, and then cooled to room temperature to obtain a yellowing-resistant quartz glue resin. The curing agent is phthalic anhydride, the antioxidant is antioxidant BHA, and the epoxy resin is purchased from Guangzhou Sanchang Chemical Co., Ltd., with a brand of E-51.
[0036] The preparation method of the modified hollow microspheres is as follows: 15 g of hollow microspheres and 60 g of 15% dilute sulfuric acid solution are mixed and stirred on a magnetic stirrer for 30 minutes, centrifuged by a centrifuge to remove the supernatant, washed with distilled water, transferred to an electric constant temperature blast drying oven, dried at a temperature of 80°C for 4 hours, mixed and stirred with 40 g of 0.2 mol / L lanthanum chloride solution at room temperature for 30 minutes, then 10 g of aluminum chloride is added and stirred for 30 minutes, washed with distilled water after centrifugation, and dried in an oven at a temperature of 80°C for 3 hours, and ground to obtain modified hollow microspheres.
[0037] Example 3
[0038] A method for preparing a yellowing-resistant quartz glue resin comprises the following steps: 50g of epoxy resin, 20g of quartz stone, and 20g of modified hollow microspheres are put into a stirrer, mixed and stirred for 10min at a speed of 1500r / min and a temperature of 65°C, and then cooled to room temperature, 2g of a curing agent and 1g of an antioxidant are added, and the temperature is raised to 40°C and stirred for 10min, and then cooled to room temperature to obtain a yellowing-resistant quartz glue resin. The curing agent is phthalic anhydride, the antioxidant is antioxidant BHT, and the epoxy resin is purchased from Guangzhou Sanchang Chemical Co., Ltd., with a brand of E-51.
[0039] The preparation method of the modified hollow microspheres is as follows: 15 g of hollow microspheres and 60 g of 15% dilute sulfuric acid solution are mixed and stirred on a magnetic stirrer for 30 minutes, centrifuged by a centrifuge to remove the supernatant, washed with distilled water, transferred to an electric constant temperature blast drying oven, dried at a temperature of 80°C for 4 hours, mixed and stirred with 40 g of 0.2 mol / L lanthanum chloride solution at room temperature for 30 minutes, then 10 g of aluminum chloride is added and stirred for 30 minutes, washed with distilled water after centrifugation, and dried in an oven at a temperature of 80°C for 3 hours, and ground to obtain modified hollow microspheres.
[0040] Example 4
[0041] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 3 in that: the method for preparing modified hollow microspheres is as follows: 45g of hollow microspheres and 80g of 15% dilute sulfuric acid solution are mixed and stirred on a magnetic stirrer for 30 minutes, centrifuged by a centrifuge to remove the supernatant, washed with distilled water, transferred to an electric constant temperature blast drying oven, dried at a temperature of 80°C for 4h, mixed and stirred with 60g of 0.2mol / L lanthanum chloride solution at room temperature for 30min, then 30g of aluminum chloride is added and stirred for 30min, washed with distilled water after centrifugation, and dried in an oven at a temperature of 80°C for 3h, and ground to obtain modified hollow microspheres.
[0042] Example 5
[0043] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 3 in that: the input amount of hollow microspheres is 30g, the input amount of lanthanum chloride solution is 54g, and the input amount of aluminum chloride is 12g.
[0044] Example 6
[0045] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 3 in that: the input amount of hollow microspheres is 30g, the input amount of lanthanum chloride solution is 57g, and the input amount of aluminum chloride is 15g.
[0046] Example 7
[0047] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 6 in that an epoxy resin is replaced with a modified epoxy resin in equal amounts, and the modified epoxy resin is prepared by mixing 10 g of silique fruit and 40 g of anhydrous ethanol, heating to 70 ° C and stirring for 2 h, adding 2 g of a titanate coupling agent, stirring for 2 h, filtering, drying in an oven at 80 ° C for 24 h, adding 20 g of an epoxy resin, stirring for 5 min, and standing for 5 min to obtain the modified epoxy resin. The titanate coupling agent is purchased from Dongguan Kangjin New Materials Co., Ltd., model NDZ-201.
[0048] Example 8
[0049] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 6 in that an epoxy resin is replaced with a modified epoxy resin in equal amounts, and the modified epoxy resin is prepared by mixing 30 g of silique fruit and 80 g of anhydrous ethanol, heating them to 70 ° C and stirring them for 2 h, then adding 6 g of a titanate coupling agent, stirring them for 2 h, filtering them, drying them in an oven at 80 ° C for 24 h, then adding 40 g of an epoxy resin, stirring them for 5 min, and standing them for 5 min to obtain the modified epoxy resin. The titanate coupling agent is purchased from Dongguan Kangjin New Materials Co., Ltd., model NDZ-201.
[0050] Example 9
[0051] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 8 in that: the input amount of Chenopodium album is 20g, the input amount of titanate coupling agent is 2.7g, and the input amount of epoxy resin is 32g.
[0052] Example 10
[0053] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 8 in that: the input amount of Chenopodium album is 20g, the input amount of titanate coupling agent is 3.6g, and the input amount of epoxy resin is 36g.
[0054] Embodiment 11
[0055] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 10 in that the input amount of the modified epoxy resin is 50g, the input amount of the quartz is 21g, and the input amount of the modified hollow microsphere is 32g.
[0056] Example 12
[0057] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 10 in that the input amount of the modified epoxy resin is 50g, the input amount of the quartz is 24g, and the input amount of the modified hollow microsphere is 36g.
[0058] Comparative Example
[0059] Comparative Example 1
[0060] A method for preparing a yellowing-resistant quartz glue resin is different from that of Example 3 in that an equal amount of modified hollow microspheres are replaced with hollow microspheres.
[0061] Comparative Example 2
[0062] A method for preparing a yellowing-resistant quartz glue resin is different from that of Example 3 in that an equal amount of modified hollow microspheres is replaced by quartz.
[0063] Comparative Example 3
[0064] A method for preparing a yellowing-resistant quartz glue resin, which is different from Example 3 in that: modified hollow microspheres are not added.
[0065] Comparative Example 4
[0066] A method for preparing a yellowing-resistant quartz glue resin is different from that of Example 3 in that an equal amount of modified hollow microspheres is replaced with talcum powder.
[0067] Performance testing:
[0068] Yellowing resistance: According to the requirements of standard GB / T 23983-2009 "Determination of yellowing resistance of wood coatings", UVA (340) lamps were used as light sources. The quartz glue resins prepared in Examples 1-12 and Comparative Examples 1-4 were placed under test conditions such that the test plate temperature was (60±3)°C, the irradiance was 0.68W / m2, and the light was continuously exposed for 168 hours. After the experiment, the color change was measured with a colorimeter. The color change value was measured in units of △E*. The smaller the measured value, the better the yellowing resistance.
[0069] Antibacterial test: According to ASTM E2149-10 "Determination of the antibacterial behavior of steady-state antibacterial agents under dynamic contact conditions", the detection index is Escherichia coli ATCC25922, and the quartz glue resin prepared in Examples 1-12 and Comparative Examples 1-4 is tested to test its antibacterial effect on Escherichia coli.
[0070] Tensile strength test: According to GB / T528-1998, a universal tensile testing machine was used to test the tensile strength of the quartz glue resins prepared in Examples 1-12 and Comparative Examples 1-4.
[0071]
[0072]
[0073] According to the data comparison of Examples 1-3 and Comparative Examples 1-4, epoxy resin is used as the main raw material, and epoxy resin itself is prone to yellowing under ultraviolet irradiation. The modified hollow microspheres and antioxidants added in the present application are evenly dispersed in the epoxy resin to improve the fluidity of the epoxy resin. The epoxy resin and the modified hollow microspheres are formed into a stable three-dimensional network structure through the curing agent. Quartz stone is used as a filler to improve the mechanical properties of the resin. The mutual coordination of various components helps to improve the yellowing resistance of the epoxy resin.
[0074] According to the data comparison of Examples 3-6, when the hollow microspheres, lanthanum chloride solution and aluminum chloride are in a specific weight ratio, the hollow microspheres themselves have high mechanical properties. After being modified by the lanthanum chloride solution, the hollow microspheres can significantly improve the interfacial compatibility with the epoxy resin substrate, enhance the bonding force between the filler and the substrate, and help improve the thermal stability and yellowing resistance of the material.
[0075] According to the data comparison of Examples 6-8, the present application achieves cross-linking of the interface between silique and epoxy resin by reacting the titanate coupling agent with the surface hydroxyl group of silique, thereby enhancing the interfacial bonding ability between silique and epoxy resin and the interaction force between molecules, thereby improving the thermal stability of the epoxy resin and further improving the yellowing resistance of the quartz glue resin.
[0076] According to the data comparison of Examples 8-10, it can be obtained that when the silique, titanate coupling agent and epoxy resin are in a specific weight ratio, the titanate coupling agent forms chemical bonds with the silique and the epoxy resin through different functional groups at both ends, thereby improving the interfacial compatibility between the silique and the epoxy resin matrix, improving the rheological properties of the epoxy resin, and making the modified epoxy resin have better yellowing resistance. Silique contains flavonoids and alkaloid compounds, which have certain antibacterial activity, thereby improving the antibacterial properties of the quartz glue resin.
[0077] According to the data comparison of Examples 10-12, when the modified epoxy resin, quartz stone and modified hollow microspheres are in a specific weight ratio, the quartz stone and modified hollow microspheres can be used as fillers to enhance the bonding force between the quartz stone and the modified hollow microspheres and the epoxy resin, and improve the yellowing resistance and mechanical properties of the glue resin.
[0078] The specific embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A yellowing-resistant quartz glue resin, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of epoxy resin; 2-6 parts of curing agent; 20-40 parts of quartz stone; 20-40 parts of modified hollow microspheres; 1-3 parts of antioxidants; The modified hollow microspheres are made of the following raw materials: hollow microspheres, dilute sulfuric acid solution, lanthanum chloride solution and aluminum chloride; The preparation method of the modified hollow microspheres comprises the following steps: mixing 15-45 parts by weight of hollow microspheres and 60-80 parts by weight of dilute sulfuric acid solution, washing after centrifugation, mixing with 40-60 parts by weight of lanthanum chloride solution after drying, adding 10-30 parts by weight of aluminum chloride and continuing to stir, washing after centrifugation, drying, and grinding to obtain the modified hollow microspheres.
2. The yellowing-resistant quartz glue resin according to claim 1, characterized in that: The particle size of the hollow microspheres ranges from 20 to 40 μm.
3. The yellowing-resistant quartz glue resin according to claim 1, characterized in that: The weight ratio of the hollow microspheres, lanthanum chloride solution and aluminum chloride is 1: (1.8-1.9): (0.4-0.5).
4. The yellowing-resistant quartz glue resin according to claim 1, characterized in that: The epoxy resin is a modified epoxy resin. The preparation method of the modified epoxy resin is as follows: 10-30 parts by weight of silique fruit and 40-80 parts by weight of anhydrous ethanol are mixed and heated, 2-6 parts by weight of a titanate coupling agent are added, stirred, filtered and dried, and then 20-40 parts by weight of an epoxy resin are added, stirred, and allowed to stand to obtain the modified epoxy resin.
5. The yellowing-resistant quartz glue resin according to claim 4, characterized in that: The weight ratio of the silique fruit, the titanate coupling agent and the epoxy resin is 1: (0.135-0.18): (1.6-1.8).
6. The yellowing-resistant quartz glue resin according to claim 4, characterized in that: The weight ratio of the modified epoxy resin, quartz stone and modified hollow microspheres is 1: (0.42-0.48): (0.64-0.72).
7. The yellowing-resistant quartz glue resin according to claim 1, characterized in that: The curing agent is one of maleic anhydride and phthalic anhydride.
8. The yellowing-resistant quartz glue resin according to claim 1, characterized in that: The antioxidant is one of the antioxidant BHT and the antioxidant BHA.
9. A method for preparing a yellowing-resistant quartz glue resin, used for preparing the yellowing-resistant quartz glue resin according to any one of claims 1 to 8, characterized in that: The following steps are involved: The epoxy resin, quartz stone and modified hollow microspheres are mixed, heated and stirred, and after cooling, a curing agent and an antioxidant are added and stirred continuously, and after cooling, a yellowing-resistant quartz stone glue resin is obtained.
Citation Information
Patent Citations
Rear-earth surface-modified hollow glass microsphere and preparation method thereof
CN102020877A
Preparation method of composite visible-light-driven photocatalyst and composite visible-light-driven photocatalyst
CN114210349A